Functional genetic encoding of sulfotyrosine in mammalian cells - Xinyuan He (Nature Portfolio, 2020)
Protein tyrosine O-sulfation is crucial for biomolecular interactions. Here the authors report in vitro engineering and in vivo validation of a tyrosyl-tRNA synthetase mutant for the genetic encoding of sulfotyrosine in mammalian cells.